Analysis of piezoelectric structures and devices - Fang, Daining, 1958-; Wang, Ji, 1962-; Chen, Weiqiu (De Gruyter, 2013)
This edited work covers piezoelectric materials in the form of beams, plates, shells, and other structural components in modern devices and structures. Applications are frequency control and detection functions in resonators, sensors, actuators, oscillations, and other smart and intelligent structures. The products and technology are with us in our daily life through computers and communication devices. The contributions cover novel methods for the analysis of piezoelectric structures including wave propagation, high frequency vibration, material characterization, and optimization of structures. Understanding of these methods is increasingly important in the design and modelling of next generation devices and micro-structures with piezoelectric elements and effects.